Electrode / electrolyte integrated device, preparation method and application thereof
Preparing current collector electrodes and printing solid electrolytes in situ through 3D printing technology solves the problems of interface stability and ion transmission speed in solid-state batteries, achieving higher energy density and faster charging and discharging speed.
Patent Information
- Application Number
- CN202510046711.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-29
AI Technical Summary
The solid interface between the electrolyte and the electrode in a solid-state battery has poor stability and the ion transmission speed is slow, which limits its charging and discharging speed.
3D printing technology is used to prepare a current collector electrode with a three-dimensional mesh structure, and mold it through impregnation and electrode ink printing to form a built-in current collector structure. At the same time, solid electrolytes are directly printed in situ on the pole sheet to improve interface stability and ion migration speed.
It significantly reduces the interface impedance, improves the lithium ion migration ability, enhances the battery's fast charging and discharge ability and cycle stability, and simplifies the battery preparation process.
Smart Images

Figure BDA0005238679850000131 
Figure BDA0005238679850000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion solid-state batteries, and in particular to an electrode / electrolyte integrated device, a preparation method and applications thereof. Background Art
[0002] Solid-state batteries have become a hot research topic in the industry due to their high energy density and high safety. However, to achieve their widespread commercial application, some key technical difficulties still need to be overcome, especially the stability of the electrolyte and electrode solid-solid interface and the problem of fast charging and discharging. The interior of a solid-state battery is composed of a solid electrolyte and an electrode, which separates the interior of the battery into two main interfaces: the solid electrolyte and the negative electrode interface, and the solid electrolyte and the positive electrode interface. These interfaces usually have some defects, such as holes, cracks, or interface mismatches, which reduce the energy density and stability of the battery. Therefore, how to optimize these interfaces and improve their stability is an important problem that solid-state batteries need to solve. Secondly, solid-state batteries also need to solve the problem of fast charging and discharging. Compared with traditional liquid batteries, solid-state batteries have slower ion transport speeds, which limits their charging and discharging speeds. Therefore, how to improve the ion transport speed of solid-state batteries and achieve fast charging and discharging is another important direction for solid-state battery research.
[0003] In order to solve these problems, researchers are conducting a lot of research work. For example, exploring new solid electrolyte materials to optimize solid-solid interface performance and ion transport characteristics. At the same time, developing new battery structures to achieve faster charging and discharging speeds, higher energy density and cycle stability.
[0004] The 3D printing technology that has emerged in recent years is leading the innovation trend in various industries. It is gradually changing the traditional manufacturing mode of batteries and bringing unprecedented possibilities and flexibility to battery design, manufacturing and application. From microstructure to macro morphology, from material compound to production process, 3D printing technology is redefining the way batteries are manufactured and promoting the battery industry to develop in a more efficient, greener and smarter direction.
[0005] The main advantages of 3D printing for preparing batteries are as follows: (1) Printing three-dimensional structures: complex three-dimensional structures can be manufactured, so that the battery materials have a higher specific surface area and pore structure, thereby improving the energy density and power density of the battery; (2) Customization: the shape and size of the battery can be customized to meet the needs of different product application scenarios; (3) Material saving: the additive manufacturing process can accurately control the amount of material used and reduce waste. At the same time, the material formula can be adjusted as needed to optimize battery performance and reduce costs; (4) Improve production efficiency: simplify the production process, reduce traditional coating, cutting, assembly and other processes, and reduce production costs.
[0006] At present, 3D printing is mainly used in the production of single components in battery manufacturing, while there is little research on the use of 3D printing for integrated printing of electrodes / solid electrolytes, which requires addressing challenges such as material formability and compatibility. Summary of the invention
[0007] The purpose of the present invention is to provide an electrode / electrolyte integrated device, a preparation method and its application in view of the above-mentioned problems. The electrode / electrolyte integrated device prepared by the present invention has good solid-solid contact stability between the electrolyte and the electrode plate interface, significantly reduces the interface impedance, and at the same time develops a mesh conductive current collector electrode built-in technology, which improves the lithium ion migration ability, reduces the weight of the current collector, and improves the electrochemical performance of the battery, especially the energy density and cycle stability.
[0008] The technical solution adopted by the present invention is as follows: a method for preparing an electrode / electrolyte integrated device, comprising the following steps;
[0009] A. Print a current collector precursor with a three-dimensional network structure by 3D printing, vacuum dry and then perform high-temperature heat treatment. The high-temperature heat treatment may be: heat treatment at 300-800°C for 2-6h in an argon or nitrogen or vacuum environment, and then cool it with the furnace or cool it down to room temperature at a cooling rate of 0.5-5°C / min to obtain;
[0010] B. Preparation of electrode ink, fast ion conductor ink and solid electrolyte ink for 3D printing;
[0011] C. Immerse the current collector in the electrode ink, take it out after immersion, squeeze out the excess electrode ink on the current collector under pressure, and then dry and solidify it. The drying and solidification can be specifically: heat and solidify it on the glass substrate through a heating pad, and the heating temperature is 25-100° C.;
[0012] D. Place the electrode ink in a 3D printing barrel, print the electrode layer on the current collector obtained in step C, and then dry and solidify it at a drying temperature of 25-100° C.
[0013] E. Place the fast ion conductor ink in a 3D printing barrel, print on the electrode layer in step D to obtain a fast ion conductor layer, and then dry and solidify at a drying temperature of 25-100° C.;
[0014] F. Place the solid electrolyte ink in a 3D printing barrel, print on the fast ion conductor layer in step E to obtain a solid electrolyte layer, and then dry and solidify at a drying temperature of 25-100° C. to obtain the solid electrolyte layer.
[0015] Further, in step A, a current collector ink is first prepared, and then a current collector precursor having a three-dimensional network structure is obtained by printing through a 3D printer, wherein the current collector ink is composed of the following components, measured by mass percentage: 70-90% of current collector material (for example, 70%, 76%, 80%, 87%, 90%, etc.), 0.1-5% of dispersant (for example, 70%, 76%, 80%, 87%, 90%, etc.), 1-12% of solvent (for example, 1%, 5%, 8%, 10%, etc.), , 12%, etc.) and 1-15% of binder (for example, 1%, 5%, 10%, 12%, 15%, etc.); the current collector material is micron- or nano-scale aluminum metal powder, the dispersant is selected from one or more of polyvinyl pyrrolidone, sodium lauryl sulfate, polyethylene glycol, and carboxymethyl cellulose; the solvent is selected from one or more of deionized water, ethanol or propanol; the binder is selected from one or more of polyvinyl alcohol, polyethylene glycol, hydroxypropyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose. When preparing the current collector ink, these components are mixed in a container, and then mechanically stirred or ball-milled to obtain the current collector ink.
[0016] Furthermore, when printing the current collector precursor, the 3D printer barrel can be set to a heating mode, the heating temperature can be set within the range of 25-100°C (the specific temperature is adjusted according to the preparation site), and then the 3D printer parameters can be set to print a micro / meso / macro three-dimensional structure of the network current collector precursor on the glass substrate according to actual needs. In order to facilitate curing and molding, a heating pad can be placed under the glass substrate to heat the glass substrate, and the heating temperature is controlled at 25-100°C (the specific temperature is adjusted according to the preparation site).
[0017] Furthermore, in the present invention, the mesh size of the current collector precursor ranges from 100 nm to 500 μm. To facilitate the subsequent impregnation process, the mesh size is preferably 200 nm to 200 μm, and more preferably 500 nm to 100 μm.
[0018] Furthermore, the electrode ink is composed of the following components, measured in mass percentage: 60-92% (for example, 60%, 70%, 80%, 85%, 92%, etc.) of powdered electrode active material, 1-5% (for example, 1%, 1.5%, 3%, 4%, 5%, etc.) of binder, 1-10% (for example, 1%, 3%, 5%, 7%, 10%, etc.) of conductive agent, and 5-30% (for example, 5%, 10%, 15%, 20%, 30%, etc.) of solvent; the electrode active material One or more selected from lithium cobalt oxide, lithium manganate, lithium iron phosphate, lithium manganese iron phosphate, nickel cobalt manganese oxide, nickel cobalt aluminum oxide; the binder is selected from one or more selected from polyethylene glycol, hydroxypropyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, vinylidene fluoride, styrene butadiene latex, styrene, butadiene; the conductive agent is selected from one or more selected from conductive carbon black, conductive graphite, carbon nanotubes, acetylene black, graphene, carbon fiber; the solvent is selected from one or more selected from water, ethanol, glycerol, N-methylpyrrolidone. When preparing the electrode ink, these components are mixed in a container, and then mixed evenly by mechanical stirring or ball milling.
[0019] Furthermore, when printing the electrode layer, the 3D printer barrel is set to a heating mode, the heating temperature is set within the range of 25-100°C (the specific temperature is adjusted according to the preparation site), and then the 3D printer parameters are set to print the electrode on the current collector. Accordingly, in order to facilitate curing and molding, a heating pad is placed under the glass substrate to heat the current collector, and the heating temperature is controlled at 25-100°C (the specific temperature is adjusted according to the preparation site) to facilitate curing and molding of the electrode layer.
[0020] Further, the fast ion conductor ink is composed of the following components in mass percentage: 60-90% of powdered fast ion conductor (for example, 60%, 70%, 80%, 85%, 90%, etc.), 5-30% of solvent (for example, 10%, 15%, 20%, 25%, 30%, etc.), and 1-15% of binder (for example, 1%, 5%, 10%, 12%, 15%, etc.); the fast ion conductor is a cubic garnet structure Li x A y B z O 12 , where A is La, Nd, Mg or Ba, B is Te, Ta, Ti, Nb, Zr, Al or In, 0<x, y, z<10; or the fast ion conductor is NASICON structure Li 1+x A x B 2-x(PO4)3, wherein A is Al, La, In or Cr, B is Ti, Ge, Zr, Hf or Sn, 0<x<2; the solvent is selected from one or more of water, ethanol, glycerol, and N-methylpyrrolidone; the binder is selected from one or more of polyethylene glycol, hydroxypropyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, vinylidene fluoride, styrene-butadiene latex, styrene, and butadiene. Accordingly, when preparing the fast ion conductor ink, these components are mixed in a container, and then uniformly mixed by mechanical stirring or ball milling. Accordingly, when printing the fast ion conductor layer, the barrel heating temperature is 25-100°C, and then the printing parameters are set to print on the electrode layer to obtain the fast ion conductor layer.
[0021] Further, in terms of mass percentage, the solid electrolyte ink is composed of the following components: 35-95% electrolyte matrix (for example, 35%, 50%, 70%, 80%, 95%, etc.), 1-40% lithium salt (for example, 1%, 10%, 20%, 30%, 40%, etc.), 1-20% inorganic filler (for example, 1%, 5%, 10%, 15%, 20%, etc.) and 1-10% organic solvent (for example, 1%, 2%, 5%, 8%, 10%, etc.); the electrolyte matrix is selected from one or more of polyethylene oxide, polypyrrole, polyethylene glycol diacrylate, polyethylene glycol, polyethylene glycol diacrylate, poly(3,4-ethylenedioxythiophene), polyacrylonitrile, polymethyl methacrylate, polymethyl acrylate, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene glycol diacrylate ; The lithium salt is selected from one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonyl imide), and lithium bis(trifluoromethylsulfonyl imide); the inorganic filler is selected from one or more of alumina, silica, lithium aluminate, barium titanate, zirconium oxide, lithium phosphorus oxynitride, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, and lithium lanthanum aluminum titanium phosphate; the organic solvent is selected from one or more of acetonitrile, ethanol, glycerol, N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethylene carbonate, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, dimethoxymethane, dimethylformamide, dimethylacetamide, polyacrylic acid, and γ-butyrolactone. Accordingly, when preparing the solid electrolyte ink, the components are mixed in a container and then uniformly mixed by mechanical stirring or ball milling. Accordingly, when printing the solid electrolyte layer, the barrel is heated to 25-100°C, and then the printing parameters are set to print on the fast ion conductor layer to obtain the solid electrolyte layer.
[0022] Further, in step C, the impregnated current collector is pressurized by a flat press to squeeze out the excess electrode ink on the current collector, and the applied pressure is 0.1-10MPa (for example, 0.1MPa, 0.5MPa, 1MPa, 5MPa, 10MPa, etc.), and the pressurization time is 1-30min, and the specific pressurization time is determined according to the actual situation. The pressure and time of pressurization should not be too large or too small. Excessive pressure or too long time will not only easily destroy the three-dimensional network structure of the current collector, but also cause excessive loss of adsorbed electrode ink and poor impregnation effect. Correspondingly, too low pressure or too short time will lead to incomplete removal of excess electrode ink, thereby affecting the bonding of the solid-solid interface between the subsequent printed electrode and the current collector, and affecting the cycle stability of the battery.
[0023] Furthermore, the thickness of the fast ion conductor layer is 5-25 μm, for example, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 25 μm, etc.
[0024] Furthermore, the present invention also includes an electrode / electrolyte integrated device, and the electrode / electrolyte integrated device is prepared by the above preparation method.
[0025] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0026] 1. The present invention has developed a mesh conductive current collector electrode built-in technology, which uses 3D printing to prepare a three-dimensional mesh current collector with a micron-level thickness, and forms a current collector built-in structure through impregnation and electrode slurry printing. This mesh design not only reduces the total weight of the battery, but also the three-dimensional micro-nanostructure mesh channel improves the uniform distribution of current, improves the battery's charge and discharge efficiency, and promotes the migration of electrons and ions;
[0027] 2. Since 3D printing cannot make the electrode material completely enter the current collector and form hollow gaps inside the current collector, thus affecting the battery energy density and cycle stability, the present invention combines the mesh conductive current collector electrode built-in technology with the impregnation process, which can completely embed part of the electrode material into the current collector, thereby avoiding the generation of gaps. At the same time, in order to avoid the solidification of excess electrode material during impregnation and affect the bonding between the subsequent printed electrode and the current collector, the excess electrode ink is removed by pressurization after impregnation, ensuring the interface bonding quality between the printed electrode and the current collector;
[0028] 3. The present invention designs a fast ion conductor layer on the surface of the electrode layer, which not only further improves the structural stability of the electrode layer and the cycle life of the battery, but also increases the migration speed of lithium ions, thereby enhancing the rapid charge and discharge capability of the battery;
[0029] 4. The present invention directly prints the solid electrolyte in situ on the electrode, which not only improves the interface stability between the electrode and the electrolyte and effectively reduces the interface impedance, but also solves the core problems of high internal resistance and insufficient high-rate discharge performance of solid-state batteries. At the same time, the present invention prepares the electrode and the solid electrolyte into an integrated device, which greatly simplifies the preparation process of the battery. Subsequently, it only needs to be assembled with a highly versatile negative electrode sheet to obtain a lithium-ion solid-state battery, thereby improving the assembly efficiency and production efficiency of the battery. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] Example 1
[0032] An electrode / electrolyte integrated device, the preparation method of which comprises the following steps:
[0033] Step 1, the current collector comprises the following components: 90% of micron-grade aluminum powder, 1% of polyvinyl pyrrolidone, 4% of deionized water and 5% of polyvinyl alcohol; the above materials are ball-milled and mixed uniformly in a container to obtain a current collector ink;
[0034] Step 2, placing the current collector ink obtained in step 1 into the barrel of a 3D printer, setting the barrel heating temperature to 40°C, setting the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and printing on a glass substrate to obtain a three-dimensional structure current collector network precursor with micro-nano meshes, the mesh size being in the range of 50μm-100μm; placing a heatable pad under the glass substrate, and controlling the temperature at 40°C;
[0035] Step 3: The printed current collector precursor is heat treated at 400° C. for 3 h under argon, and then cooled to room temperature in the furnace to obtain a current collector with a thickness of 10 μm;
[0036] Step 4, preparing electrode ink, which is composed of the following components: 82% of NCM811 active material, 5% of carboxymethyl cellulose, 10% of deionized water, and 3% of acetylene black; mixing the above materials, and ball-milling the above materials in a container to obtain electrode ink;
[0037] Step 5, immersing the current collector in the electrode ink prepared in step 4 for 20 minutes, then taking it out, and pressurizing the impregnated current collector with a flat press at a pressure of 6 MPa for 3 minutes to squeeze out excess electrode ink on the current collector, and then drying to obtain the impregnated current collector;
[0038] Step 6, placing the electrode ink obtained in step 4 in the barrel of a 3D printer, setting the barrel heating temperature to 40°C, setting the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and printing the electrode layer on the current collector obtained in step 5 with a thickness of 30μm; placing a heatable pad under the current collector, controlling the temperature at 80°C, and forming an electrode built into the current collector after drying;
[0039] Step 7: Prepare a fast ion conductor ink, which consists of the following components: Li7La3Zr2O 12 The fast ion conductor ink is obtained by mixing 85% of iodine, 10% of deionized water and 5% of carboxymethyl cellulose with mechanical stirring;
[0040] Step 8: Place the fast ion conductor ink in the 3D printer barrel, set the barrel heating temperature to 40°C, set the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and print the fast ion conductor layer on the electrode surface with a thickness of 20μm;
[0041] Step 9, preparing a solid electrolyte ink, which is composed of the following components: 80% of polyvinylidene fluoride-hexafluoropropylene, 10% of lithium bis(trifluoromethylsulfonyl)imide, 5% of lithium lanthanum zirconium aluminum oxide and 5% of acetonitrile, and mixing them evenly by magnetic stirring to obtain a solid electrolyte ink;
[0042] Step 10: Place the solid electrolyte ink in the 3D printer barrel, set the barrel heating temperature to 40°C, set the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and continue to print the solid electrolyte on the fast ion conductor layer with a thickness of 20μm, thereby preparing an electrode / electrolyte integrated device.
[0043] The prepared electrode / electrolyte integrated device was vacuum dried at 180°C for 24 h and assembled into a battery with metal lithium foil in a glove box for testing.
[0044] Example 2
[0045] Example 2 is the same as Example 1, except that the mesh size of the current collector is 80-150 μm and the thickness is 20 μm.
[0046] Example 3
[0047] An electrode / electrolyte integrated device, the preparation method of which comprises the following steps:
[0048] Step 1, the current collector comprises the following components: 90% of micron-grade aluminum powder, 1% of polyvinyl pyrrolidone, 4% of deionized water and 5% of polyvinyl alcohol; the above materials are ball-milled and mixed uniformly in a container to obtain a current collector ink;
[0049] Step 2, placing the current collector ink obtained in step 1 into the barrel of a 3D printer, setting the barrel heating temperature to 40°C, setting the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and printing on a glass substrate to obtain a three-dimensional structure current collector network precursor with micro-nano meshes, the mesh size being in the range of 50μm-100μm; placing a heatable pad under the glass substrate, and controlling the temperature at 40°C;
[0050] Step 3: The printed current collector precursor is heat treated at 400° C. for 3 h under argon, and then cooled to room temperature in the furnace to obtain a current collector with a thickness of 20 μm;
[0051] Step 4, preparing electrode ink, which is composed of the following components: 85% lithium iron phosphate active material, 4% carboxymethyl cellulose, 8% deionized water, and 3% acetylene black; mixing the above materials, and ball-milling the above materials in a container to obtain electrode ink;
[0052] Step 5, immersing the current collector in the electrode ink prepared in step 4 for 20 minutes, then taking it out, and pressurizing the immersed current collector with a flat press at a pressure of 5 MPa for 3 minutes to squeeze out excess electrode ink on the current collector, and then drying to obtain an immersed current collector;
[0053] Step 6, placing the electrode ink obtained in step 4 in the barrel of a 3D printer, setting the barrel heating temperature to 40°C, setting the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and printing the electrode layer on the current collector obtained in step 5 with a thickness of 50μm; placing a heatable pad under the current collector, controlling the temperature at 80°C, and forming an electrode built into the current collector after drying;
[0054] Step 7: Prepare a fast ion conductor ink, which consists of the following components: Li7La3Zr2O 12 The fast ion conductor ink is obtained by mixing 85% of iodine, 10% of deionized water and 5% of carboxymethyl cellulose with mechanical stirring;
[0055] Step 8: Place the fast ion conductor ink in the 3D printer barrel, set the barrel heating temperature to 40°C, set the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and print the fast ion conductor layer on the electrode surface with a thickness of 20μm;
[0056] Step 9, preparing a solid electrolyte ink, which is composed of the following components: 80% of polyvinylidene fluoride-hexafluoropropylene, 10% of lithium bis(trifluoromethylsulfonyl)imide, 5% of lithium lanthanum zirconium aluminum oxide and 5% of acetonitrile, and mixing them evenly by magnetic stirring to obtain a solid electrolyte ink;
[0057] Step 10: Place the solid electrolyte ink in the 3D printer barrel, set the barrel heating temperature to 40°C, set the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and continue to print the solid electrolyte on the fast ion conductor layer with a thickness of 30μm, thereby preparing an electrode / electrolyte integrated device.
[0058] The prepared electrode / electrolyte integrated device was vacuum dried at 180°C for 24 h and assembled into a battery with metal lithium foil in a glove box for testing.
[0059] Example 4
[0060] An electrode / electrolyte integrated device, the preparation method of which comprises the following steps:
[0061] Step 1, the current collector comprises the following components: 90% of micron-grade aluminum powder, 1% of polyvinyl pyrrolidone, 4% of deionized water and 5% of polyvinyl alcohol; the above materials are ball-milled and mixed uniformly in a container to obtain a current collector ink;
[0062] Step 2, placing the current collector ink obtained in step 1 into the barrel of a 3D printer, setting the barrel heating temperature to 40°C, setting the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and printing on a glass substrate to obtain a three-dimensional structure current collector network precursor with micro-nano meshes, the mesh size being in the range of 50μm-100μm; placing a heatable pad under the glass substrate, and controlling the temperature at 40°C;
[0063] Step 3: The printed current collector precursor is heat treated at 400° C. for 3 h under argon, and then cooled to room temperature to obtain a current collector with a thickness of 30 μm.
[0064] Step 4, preparing electrode ink, which is composed of the following components: 82% lithium-rich manganese-based active material, 5% carboxymethyl cellulose, 10% deionized water, and 3% acetylene black; mixing the above materials, and ball-milling the above materials in a container to obtain electrode ink;
[0065] Step 5, immersing the current collector in the electrode ink prepared in step 4 for 20 minutes, then taking it out, and pressurizing the impregnated current collector with a flat press at a pressure of 6 MPa for 3 minutes to squeeze out excess electrode ink on the current collector, and then drying to obtain the impregnated current collector;
[0066] Step 6, placing the electrode ink obtained in step 4 in the barrel of a 3D printer, setting the barrel heating temperature to 40°C, setting the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and printing an electrode layer on the current collector obtained in step 5 with a thickness of 50μm; placing a heatable pad under the current collector, and controlling the temperature at 80°C; the electrode ink is evenly distributed in the current collector network, and after drying, an electrode built into the current collector is formed;
[0067] Step 7: Prepare fast ion conductor ink, which consists of the following components: Li 1.3 Al 0.3 Ti 1.7 (PO4)3 is 87%, deionized water is 9%, and carboxymethyl cellulose is 4%, and the mixture is stirred mechanically to obtain a fast ion conductor ink;
[0068] Step 8: Place the fast ion conductor ink in the 3D printer barrel, set the barrel heating temperature to 40°C, set the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and print the fast ion conductor layer on the electrode surface with a thickness of 10μm;
[0069] Step 9, preparing a solid electrolyte ink, which is composed of the following components: 80% of polyvinylidene fluoride-hexafluoropropylene, 10% of lithium bis(trifluoromethylsulfonyl)imide, 5% of lithium lanthanum zirconium aluminum oxide and 5% of acetonitrile, and mixing them evenly by magnetic stirring to obtain a solid electrolyte ink;
[0070] Step 10: Place the solid electrolyte ink in the 3D printer barrel, set the barrel heating temperature to 40°C, set the printer parameters, the ink outflow rate to 15mL / min, the needle printing speed to 50mm / s, and continue to print the solid electrolyte on the fast ion conductor layer with a thickness of 20μm, thereby preparing an electrode / electrolyte integrated device.
[0071] The prepared electrode / electrolyte integrated device was vacuum dried at 180°C for 24 h and assembled into a battery with metal lithium foil in a glove box for testing.
[0072] Comparative Example 1
[0073] Comparative Example 1 is the same as Example 1, except that after impregnation, the excess electrode ink is not removed by pressurization using a flat press, but the impregnated current collector is directly dried.
[0074] Comparative Example 2
[0075] Comparative Example 2 is the same as Example 1, except that no impregnation process is performed, that is, step 5 is not performed, but the electrode is directly printed on the current collector by 3D printing.
[0076] Comparative Example 3
[0077] Comparative Example 3 is the same as Example 1, except that when the pressure is applied by the flat plate, the pressure applied is 13 MPa.
[0078] Comparative Example 4
[0079] Comparative Example 4 is the same as Example 1, except that the mesh size of the current collector is 600 μm.
[0080] Comparative Example 5
[0081] Comparative Example 5 is the same as Example 1, except that the current collector is an aluminum foil with the same thickness, and the electrode layer is coated on the aluminum foil by conventional coating.
[0082] Test analysis and results
[0083] The solid-state lithium-ion batteries obtained in Examples 1-4 and Comparative Examples 1-5 were subjected to electrochemical performance tests (charge and discharge tests were performed on a Land charge and discharge test instrument). The test voltage of the ternary material was 2.8-4.5V (1C=200mAh / g); the test voltage of the lithium-rich material was 2.5-4.8V (1C=250mAh / g); and the test voltage of the LiFePO4 material was 2.5-3.65V (1C=165mAh / g). The test results are shown in Table 1.
[0084] Table 1 Electrochemical performance test results of examples and comparative examples
[0085]
[0086]
[0087] It can be seen from Table 1 that the battery impedance in Example 1 is lower than that in Comparative Examples 1-5, which shows that the internal resistance of the battery can be effectively reduced by optimizing the process, such as impregnation and three-dimensional current collector integration. Secondly, the discharge capacity, coulomb efficiency and cycle performance of Example 1 are higher than those of Comparative Examples 1-5, which shows that the integrated device design helps to improve the charge and discharge efficiency and capacity retention rate of the battery. From the test results of Comparative Examples 1-5, it can be seen that the excess electrode ink was not removed in Comparative Example 1, the impregnation process was not performed in Comparative Example 2, and excessive pressure was applied to Comparative Example 3, all of which led to a decrease in battery performance. The mesh size of the current collector in Comparative Example 4 was too large, which also affected the overall performance of the battery. Comparative Example 5 used traditional aluminum foil instead of 3D printed current collectors, and its performance was not as good as that of Example 1, which emphasized the advantages of 3D printing technology in the preparation of current collectors. In addition, the optimization of fast ion conductors and solid electrolytes is also critical. Their thickness and composition have a significant effect on battery performance. In the embodiment, a current collector with ideal performance is prepared by precisely controlling the heat treatment temperature and time. These laws show that the electrochemical performance of solid-state lithium-ion batteries can be significantly improved through material selection, process parameter control and design. At the same time, this also confirms the potential and importance of 3D printing technology in the development of high-performance battery current collectors.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an electrode / electrolyte integrated device, characterized in that: The steps include: A. Printing a current collector precursor with a three-dimensional network structure by 3D printing, and then vacuum drying and high-temperature heat treatment to obtain a current collector; B. Preparation of electrode ink, fast ion conductor ink and solid electrolyte ink for 3D printing; C. Immerse the current collector in the electrode ink, take it out after immersion, squeeze out the excess electrode ink on the current collector under pressure, and then dry and solidify it; D. placing the electrode ink in a 3D printing barrel, printing the electrode layer on the current collector obtained in step C, and then drying and curing; E. placing the fast ion conductor ink in a 3D printing barrel, printing on the electrode layer in step D to obtain a fast ion conductor layer, and then drying and curing; F. Place the solid electrolyte ink in a 3D printing barrel, print on the fast ion conductor layer in step E to obtain a solid electrolyte layer, and then dry and solidify to obtain.
2. The preparation method according to claim 1, characterized in that In step A, a current collector ink is first prepared, and then a current collector precursor having a three-dimensional network structure is obtained by printing through a 3D printer, wherein the current collector ink is composed of the following components, measured in mass percentage: 70-90% of current collector material, 0.1-5% of dispersant, 1-12% of solvent and 1-15% of binder; the current collector material is micron- or nano-scale aluminum metal powder, the dispersant is selected from one or more of polyvinyl pyrrolidone, sodium dodecyl sulfate, polyethylene glycol, and carboxymethyl cellulose; the solvent is selected from one or more of deionized water, ethanol or propanol; the binder is selected from one or more of polyvinyl alcohol, polyethylene glycol, hydroxypropyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose.
3. The preparation method according to claim 1, characterized in that: In terms of mass percentage, the electrode ink is composed of the following components: 60-92% of powdered electrode active material, 1-5% of binder, 1-10% of conductive agent and 5-30% of solvent; the electrode active material is selected from one or more of lithium cobalt oxide, lithium manganate, lithium iron phosphate, lithium manganese iron phosphate, nickel cobalt manganese oxide (including lithium-rich manganese-based oxide), and nickel cobalt aluminum oxide; the binder is selected from one or more of polyethylene glycol, hydroxypropyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, vinylidene fluoride, styrene-butadiene latex, styrene, and butadiene; the conductive agent is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes, acetylene black, graphene, and carbon fiber; the solvent is selected from one or more of water, ethanol, glycerol, and N-methylpyrrolidone.
4. The preparation method according to claim 1, characterized in that: The fast ion conductor ink is composed of the following components in terms of mass percentage: 60-90% powdered fast ion conductor, 5-30% solvent, and 1-15% binder; the fast ion conductor is a cubic garnet structure Li x A y B z O 12 , where A is La, Nd, Mg or Ba, B is Te, Ta, Ti, Nb, Zr, Al or In, 0<x, y, z<10; or the fast ion conductor is NASICON structure Li 1+x A x B 2-x (PO4)3, wherein A is Al, La, In or Cr, B is Ti, Ge, Zr, Hf or Sn, and 0<x<2; the solvent is selected from one or more of water, ethanol, propylene glycol, and N-methylpyrrolidone; the binder is selected from one or more of polyethylene glycol, hydroxypropyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, vinylidene fluoride, styrene-butadiene latex, styrene, and butadiene.
5. The preparation method according to claim 1, characterized in that: In terms of mass percentage, the solid electrolyte ink is composed of the following components: 35-95% electrolyte matrix, 1-40% lithium salt, 1-20% inorganic filler and 1-10% organic solvent; the electrolyte matrix is selected from one or more of polyethylene oxide, polypyrrole, polyethylene glycol diacrylate, polyethylene glycol, polyethylene glycol diacrylate, poly(3,4-ethylenedioxythiophene), polyacrylonitrile, polymethyl methacrylate, polymethyl acrylate, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene glycol diacrylate; the lithium salt is selected from lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, One or more of lithium bis(trifluoromethylsulfonyl)imide; the inorganic filler is selected from one or more of alumina, silica, lithium aluminate, barium titanate, zirconium oxide, lithium phosphorus oxynitride, lithium lanthanum titanate, lithium lanthanum zirconium oxy, and lithium lanthanum aluminum titanium phosphate; the organic solvent is selected from one or more of acetonitrile, ethanol, glycerol, N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethylene carbonate, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, dimethoxymethane, dimethylformamide, dimethylacetamide, polyacrylic acid, and γ-butyrolactone.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step C, the impregnated current collector is pressurized by a flat press to squeeze out excess electrode ink on the current collector. The applied pressure is 0.1-10 MPa and the pressurization time is 1-30 min.
7. The preparation method according to claim 6, characterized in that: In the current collector precursor having a three-dimensional network structure, the mesh size is 100nm-500μm.
8. The preparation method according to claim 6, characterized in that: The thickness of the fast ion conductor layer is 5-25 μm.
9. An electrode / electrolyte integrated device, characterized in that: The electrode / electrolyte integrated device is prepared by the preparation method described in any one of claims 1 to 8 above.
10. Application of an electrode / electrolyte integrated device in a lithium-ion solid-state battery, characterized in that: The electrode and solid electrolyte of the lithium-ion solid-state battery are the electrode / electrolyte integrated device as described in claim 9.